(untitled) (Archives of Mechanics - Test, 2008)
This paper reports about an experimental investigation of the wake behind a solid sphere on a low velocity hydrodynamical channel for the Reynolds number in the range 250–310. The aim of the work is to analyze the size and shape of the vortices’ cores and its change as a function of the Reynolds number. Special attention is paid to the transition from stationary flow, characterized by two counter-rotating longitudinal vortices, to instationary flow. The two-coloured visualization of the wake in steady and unsteady regimes is also presented.